EDUCATION OF PARTICIPANTS IN MAP SECTOR WITH AN AIM TO IMPROVE MARKET COMPETITIVENESS AND RURAL DEVELOPMENT IN SERBIA - Turudija-Živanović, Svetlana; Živanović, Tomislav; Marković, Tatjana (Economics of Agriculture, 2018)
There are many problems appearing in MAP sector during collection, growing and marketing of medicinal and aromatic plants, such as: decrease in number of plant collectors, absence of licensed plant collectors, decrease in the surface under medicinal and aromatic, absence of subventions in large-scale production, ignorance and restrictiveness of the low regulations that treat this field, etc. All of these directly influence concurrency of the MAP sector on domestic and foreign market and indirectly slow down rural development of Serbia. Special attention in education of MAP sector participant should be devoted to the low regulations. It is normatively regulated by many lows and low regulations (more then 130 different low regulations). However, the environment and nature protection is the filed where many regulations are not yet harmonized with European Union regulations. Following adoption of the low on the nature protection the application of Decree on control of use and turnover of wild flora and fauna ("Službeni glasnik RS", no. 31/2005 from 8.4.2005).